PERKEMBANGAN MORAL TOKOH KIKI USIA 10-14 TAHUN DALAM NOVEL MAJO NO TAKKYUUBIN KARYA EIKO KADONO - Eka Savitri, Ni Putu Ayu (Humanis, 2016)
This study titled Moral Development of Kiki Aged 10-14 years in the novel Majo No Takkyuubin by EikoKadono. The purposes of this study were to determine the moral development and character formation of Kiki in novel Majo No Takkyuubin by EikoKadono. The method used in this study were descriptive analysis methods and formal methods. The theory used were the theory of moral development by Kohlberg and Japanese morality theory by Morita. The result shows that there are three levels of moral development in Kiki and each level has two phases. The first level is praconventional level which divided into punishment and obedience orientation and instrumental relativist orientation phase. The second level is conventional level which divided into sweet child orientation phase and penalty and order phase. The third level is post-conventional level which divided into social contract legalistic orientation phase and universal ethical principle orientation phase. This study also shows Kiki’s four character formations based on the theory proposed by Morita. Those four character formationsareganbaru, shitsuke, sunao, and kuukiwoyomu. Also there are seven character formation of Kiki based on the principle of life of bushido, namely: makoto, jin, gi, rei, meiyo, chuugi, and yuu.
Keywords: moral development, character formation, psychology literature.